Utility of the clue — From assessing the investigative contribution of forensic science to supporting the decision to use traces. Issue 6 (December 2015) - Bitzer, Sonja; Albertini, Nicola; Lock, Eric; Ribaux, Olivier; Delémont, Olivier
Abstract: In an attempt to grasp the effectiveness of forensic science in the criminal justice process, a number of studies introduced some form of performance indicator. However, most of these indicators suffer from different weaknesses, from the definition of forensic science itself to problems of reliability and validity. We suggest the introduction of the concept of utility of the clue as an internal evaluation indicator of forensic science in the investigation. Utility of the clue is defined as added value of information, gained by the use of traces. This concept could be used to assess the contribution of the trace in the context of the case. By extension, a second application of this concept is suggested. By formalising and considering, a priori, the perceived utility of using traces, we introduce the notion of expected utility that could be used as decision factor when choosing which traces to use, once they have been collected at the crime scene or from an object in the laboratory. In a case-based approach, utility can be assessed in the light of the available information to evaluate the investigative contribution of forensic science. In the decision-making process, the projection or estimation of the utility of the clue is proposed to be a factor to take into account when triaging the set of traces. Highlights: Contribution assessment of forensic science needs the definition of valid indicators. These need to account for the diverse levels of use of traces in judicial inquiries. We suggest the introduction of the utility of the clue as such an indicator. Utility of the clue could be used to assess investigative impacts of forensic science. It could also be used to support the decision making process.